Lessons Learned in Establishing a University Global Course - Hedberg, Karl; Tanner, Paul (Journal of NELTA, 2023)
This paper outlines the creation, implementation, and subsequent development of a Global Leadership course at a national university in Japan. In 2014, our university in central Japan, with the encouragement of Japan’s Ministry of Education, established a Global Leadership course for elite students. The purpose was to foster leadership and develop relations with other Asian countries using English. Students accepted into the program take supplementary English classes and participate in a foreign internship. The application was open to all matriculated graduates. Since the establishment of the Global Course, adjustments have been made to improve the application procedure, academic rigor, and assessment. The authors address the adaptations that have been made to improve the Global Course program, particularly the application process and method of selection as well as some changes made to the curriculum.